2022
DOI: 10.3390/psych4040059
|View full text |Cite
|
Sign up to set email alerts
|

A Failed Cross-Validation Study on the Relationship between LIWC Linguistic Indicators and Personality: Exemplifying the Lack of Generalizability of Exploratory Studies

Abstract: (1) Background: Previous meta-analytic research found small to moderate relationships between the Big Five personality traits and different linguistic computational indicators. However, previous studies included multiple linguistic indicators to predict personality from an exploratory framework. The aim of this study was to conduct a cross-validation study analyzing the relationships between language indicators and personality traits to test the generalizability of previous results; (2) Methods: 643 Spanish un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Argamon and Levitan (2005) and Oberlander and Gill (2006) also used this approach and found that word usage could identify the trait of extroversion in writers. Martínez-Huertas, et al (2022) reported that LIWC variables had a significant relationship with big five personality traits (openness, conscientiousness, extraversion, agreeableness, and neuroticism) in their sample. Pennebaker and King (1999) and Pennebaker (2011) have written extensively about the relationship between the personality traits associated with writing style.…”
Section: Discussionmentioning
confidence: 94%
“…Argamon and Levitan (2005) and Oberlander and Gill (2006) also used this approach and found that word usage could identify the trait of extroversion in writers. Martínez-Huertas, et al (2022) reported that LIWC variables had a significant relationship with big five personality traits (openness, conscientiousness, extraversion, agreeableness, and neuroticism) in their sample. Pennebaker and King (1999) and Pennebaker (2011) have written extensively about the relationship between the personality traits associated with writing style.…”
Section: Discussionmentioning
confidence: 94%
“…This study, published in five volumes as Genetic Studies of Genius between 1926 and 1959, required the construction of a special instrument to accommodate Terman's subjects as adults, called the Concept Mastery Test [3]. This marked the beginning of experimental research on adults in the intellectual stratosphere using psychological techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Martínez-Huertas, Moreno, Olmos, Martínez-Mingo, and Jorge-Botana (2022) titled "A failed cross-validation study on the relationship between LIWC linguistic indicators and personality: Exemplifying the lack of generalizability of exploratory studies" [3] is a replication study to study the relationship between the "Big 5 personality traits" and linguistic indicators. In a sample of N = 643 Spanish undergraduate students, it was found that language and personality relationships were not generalizable in crossvalidation studies.…”
Section: Introductionmentioning
confidence: 99%